The Efforts of Lombok Regency Government to Recovery After the 2018 Lombok Earthquake Disaster - Miftakhudin Ahmad; Pujo Widodo; Sugeng Tri Utomo; Kusuma, Kusuma (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The purpose of the Indonesian nation and state, as stated in the Preamble of the 1945 Constitution of the Republic of Indonesia, is the protection of the entire Indonesian Nation, the Indonesian homeland, and the advancement of general welfare. National security is essential in achieving these goals, especially in protecting against various threats, including natural disasters. Earthquakes are one of the main threats because Indonesia is located at the confluence of three active earth plates.  The purpose of this research was to identify the efforts made by local governments in reducing the risk of natural disasters in NTB Province. The method used in this research was qualitative, with data collection techniques such as interviews, observations, and document studies. Data analysis was conducted using descriptive methods. The result of the research was the post-disaster recovery of the 2018 Lombok earthquake, involving the social and economic sectors. The rebuilding of education, health, and worship facilities was included in the social sector recovery. Economic sector recovery focused on supporting Micro, Small, and Medium Enterprises (MSMEs), agriculture, fisheries, livestock, trade, and tourism. The Disaster Resilient Village program was enhanced, with special attention to the sustainability of earthquake-resistant development. This research provided further understanding of local government efforts to deal with natural disaster risk in NTB Province, offering guidance for other regions facing similar challenges.